Kepuasan Masyarakat Terhadap Pelayanan Dokumen Admindukcapil Kota Blitar Dengan Menggunakan Aplikasi www.SIPAK.blitarkota.go.id - Rahayu, Ida (Otonomi, 2021)
This study aims to analyze the influence of service and product quality on the satisfaction of community as the user of population administration and civil registration document service who use the service application www.sipak.blitarkota.go.id at the Department of Population and Civil Registration of Blitar City. This service application was launched in 2020 as one of the efforts in optimalizing population administration service during Covid-19 pandemic which forced public service institutions to provide an excellent service consistently by limiting direct contact with the service users community. The type of research had been done is descriptive research using quantitative approach while the data analysis technique used is double regression. Population and sample of this research the service users community on 23 to 27 November 2020 where the sample was determined using Solvin’s formula as many as 83 people or 16% out of 494 service users. The result of the study showed that service quality (X1) had significant influence on the community satisfaction (Y), as well as product quality (X2) had significant influence on the community satisfaction (Y) . However, the overall dominant correlation is strongly given by the service quality compared to the product quality.